Psychometric properties of the faces version of the Malay-modified child dental anxiety scale - Esa, R.; Hashim, N.A.; Ayob, Y.; Yusof, Z.Y.M. (BioMed Central, 2015)

(untitled)
Background: To evaluate the psychometric properties of the faces version of the Modified Child Dental Anxiety Scale (MCDAS(f)) Malay version in 5-6 and 9-12 year-old children. Methods: The MCDASf was cross culturally adapted from English into Malay. The Malay version was tested for reliability and validity in 3 studies. In the Study 1, to determine test-retest reliability of MCDASf scale, 166 preschool children aged 5-6 years were asked to rank orders five cartoons faces depicting emotions from 'very happy' to 'very sad' faces on two separate occasions 3 weeks apart. A total of 87 other 5-6 year-old children completed the Malay-MCDAS(f) on two separate occasions 3 weeks apart to determine test-retest reliability for Study 2. In study 3, 239 schoolchildren aged 9-12 years completed the Malay-MCDASf and the Malay-Dental Subscale of the Children Fear Survey Schedule (CFSS-DS) at the same sitting to determine the criterion and construct validity. Results: In study 1, Kendall W test showed a high degree of concordance in ranking the cartoon faces picture cards on each of the 2 occasions (time 1, W = 0.955 and time 2, W = 0.954). The Malay-MCDASf demonstrated moderate test-retest reliability (Intraclass correlation coefficient = 0.63, p < 0.001) and acceptable internal consistency for all the 6 items (Cronbach's alpha = 0.77) and 8 items (Cronbach's alpha = 0.73). The highest MCDASf scores were observed for the items 'injection in the gum' and 'tooth taken out' for both age groups. The MCDASf significantly correlated with the CFSS-DS (Pearson r = 0.67, p < 0.001). Conclusions: These psychometric findings support for the inclusion of a cartoon faces rating scale to assess child dental anxiety and the Malay-MCDASf is a reliable and valid measure of dental anxiety in 5-12 year-old children.